Hijacking SARS-CoV-2/ACE2 Receptor Interaction by Natural and Semi-synthetic Steroidal Agents Acting on Functional Pockets on the Receptor Binding Domain - Carino, Adriana; Moraca, Federica; Fiorillo, Bianca; Marchianò, Silvia; Sepe, Valentina; Biagioli, Michele; Finamore, Claudia; Bozza, Silvia; Francisci, Daniela; Distrutti, Eleonora; Catalanotti, Bruno; Zampella, Angela; et al. (Frontiers in Chemistry, 2020)
The coronavirus disease 2019 (COVID-19) is a respiratory tract infection caused by the severe acute respiratory syndrome coronavirus (SARS)-CoV-2. In light of the urgent need to identify novel approaches to be used in the emergency phase, we have embarked on an exploratory campaign aimed at repurposing natural substances and clinically available drugs as potential anti-SARS-CoV2-2 agents by targeting viral proteins. Here we report on a strategy based on the virtual screening of druggable pockets located in the central β-sheet core of the SARS-CoV-2 Spike's protein receptor binding domain (RBD). By combining an in silico approach and molecular in vitro testing we have been able to identify several triterpenoid/steroidal agents that inhibit interaction of the Spike RBD with the carboxypeptidase domain of the Angiotensin Converting Enzyme (ACE2). In detail, we provide evidence that potential binding sites exist in the RBD of the SARS CoV-2 Spike protein and that occupancy of these pockets reduces the ability of the RBD to bind to the ACE2 consensus in vitro. Naturally occurring and clinically available triterpenoids such as glycyrrhetinic and oleanolic acids, as well as primary and secondary bile acids and their amidated derivatives such as glyco-ursodeoxycholic acid and semi-synthetic derivatives such as obeticholic acid reduces the RBD/ACE2 binding. In aggregate, these results might help to define novel approaches to COVID-19 based on SARS-CoV-2 entry inhibitors.